Two new species and two new synonyms of Systropus Wiedemann, 1820 from Palaearctic China (Diptera: Bombyliidae) - Cui, Weina; Yang, Ding (Zootaxa, 2010)
The following two new species of the genus Systropus Wiedemann, 1820 from China are described: Systropus brochus sp. nov., Systropus coalitus sp. nov.. Two new synonyms, Systropus beijinganus Du & Yang, syn. nov. of Systropus hoppo Matsumura, 1916 and Systropus oestrus Du & Yang, syn. nov. of Systropus chinensis Bezzi, 1905, are provided. A key to the species of the genus from Palaearctic China is presented.